Impact of an intermittent and localized cooling intervention on skin temperature, sleep quality and energy expenditure in free-living, young, healthy adults. (April 2021) - Xu, Huiwen; Martinez-Nicolas, Antonio; Martinez-Avila, Wendy D.; Alcantara, Juan M.A.; Corral-Perez, Juan; Jimenez-Pavon, David; Acosta, Francisco M.; Ruiz, Jonatan R.; Martinez-Tellez, Borja
Abstract: Where people live and work together it is not always possible to modify the ambient temperature; ways must therefore be found that allow individuals to feel thermally comfortable in such settings. The Embr Wave® is a wrist-worn device marketed as a 'personal thermostat' that can apply a local cooling stimulus to the skin. The aim of the present study was to determine the effect of an intermittent mild cold stimulus of 25 °C for 15–20 s every 5 min over 3.5 days under free-living conditions on 1) skin temperature, 2) perception of skin temperature, 3) sleep quality and 4) resting energy expenditure (REE) in young, healthy adults. Ten subjects wore the device for 3.5 consecutive days. This intervention reduced distal skin temperature after correcting for personal ambient temperature (P < 0.05), but did not affect the subjects' the perception of skin temperature, sleep quality or REE (all P ≥ 0.051). Thus, this intermittent mild cold regime can reduce distal skin temperature, and wearing it under free-living conditions for 3.5 days does not seem to impair the perception of skin temperature and sleep quality or modify REE. Highlights: An intermittent cold regime reduces distal skin temperature after 3.5 days. An intermittent cold regime does not modify perception of skin temperature after 3.5 days. An intermittent cold regime does not impair sleep quality after 3.5 days. An intermittent cold regime does not modify resting energy expenditure after 3.5 days. Abstract : New & noteworthy: Cold exposure has been suggested as an effective therapy for improving metabolic health, but better study interventions are needed. This study provides evidence that an intermittent mild cold regimen on the right wrist is able to decrease distal skin temperature in both hands after 3.5 days activation, yet other metabolic parameters were not affected.